Impact of modified kenaf fibers on shrinkage and cracking of cement pastes. (20th December 2020) - Guo, Aofei; Sun, Zhihui; Satyavolu, Jagannadh
Highlights: Effect of modified kenaf fibers on shrinkage of cement pastes was investigated. Effect of modified kenaf fibers on cracking of cement pastes was studied. Effect of fiber dosage on shrinkage and cracking of cement pastes was examined. Effect of fiber type on shrinkage and cracking of cement pastes was discussed. Abstract: In this study, raw, alkaline treated, and alkaline-hydrogen peroxide treated kenaf fibers were utilized in cement paste in order to evaluate their impact on shrinkage and cracking of the paste. Specifically, the effect of fiber dosage and type of fiber modification on autogenous shrinkage and drying shrinkage cracking of cement pastes were studied. The results show that the addition of kenaf fibers can reduce the autogenous shrinkage and drying shrinkage cracking of cement pastes significantly, with 0.5% fiber dosage performing better than 0.25% fiber dosage. Of all three types of kenaf fibers, alkaline-hydrogen peroxide treated kenaf fibers can reduce autogenous shrinkage and drying shrinkage cracking the most. By comparing raw kenaf fibers and alkaline treated kenaf fibers, when 0.25% kenaf fibers are used, alkaline treated kenaf fibers can reduce autogenous shrinkage more but reduce drying shrinkage cracking less; however, when 0.5% kenaf fibers are used, alkaline treated kenaf fibers can reduce both autogenous shrinkage and drying shrinkage cracking more.